Gn. Manlius Vulso’s March through Thrace in 188 B.C. according to Livy’s manuscript tradition (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2021)
This paper draws attention to some features of the manuscript tradition of Livy’s account about the movement of the Roman troops under the command of Gnaeus Manlius Vulso from the Thracian Chersonese towards the Hebrus River. A strict adherence to the manuscripts is proposed and several widely accepted adjustments are questioned. Presented are some doubts in the reading of Gypseia as Cypsela. It is suggested a relation between the Thracians Corneli(i) and the Scipiones. Emphasized is the incorrect replacement of the phrase “templum Mendidium”, attested in all of the available codices, with “templum Bendidium” by the modern scholars and are presented arguments for a connection of that temple with the Ionian settlement of Mende, which is mentioned by some ancient authors in the downstream area of Hebrus River, not far from Aenos.
Keywords: Ancient Thrace; Romans; military operations; manuscripts